Competitive positioning of commercial banks on the base of innovative banking services and technologies : case study in Russia - Reznichenko, Lea; Guseynova, Yulia (Universitetet i Nordland, 2012)
Masteroppgave i bedriftsøkonomi - Universitetet i Nordland, 2012 This research discusses the competitive advantages that commercial banks get from the usage of innovative technologies. The technological change and financial innovation that banking sphere has experienced during the past years is discussed in the first place. This thesis gives the understanding of such innovations as an online banking in the modern foreign banks and their possible application in Russia and influence on the competitive positions of banks on the Russian banking market. The CUffent state and prospects in development of Internet technology in Russia, the obstacles and problems of its development are discussed on the base of broad literature and statistical review. Furthermo re , the study seeks to get a deeper understanding of the ways the banks improve their competitive positions with the development of innovative internet banking services and the use of new technology strategy in the banking sector. In order to answer the research question case studies are conducted using several interviews with managers of the three largest Russian banks, directly participating in the choose of the strategy of internet usage these banks are: VTB Group, Alfa-Bank and Citibank. During the analysis the propositions are proven that the widespread introduction of new technologies provides credit institutions with significant increase of their efficiency, expand the range of its services, improvement of their quality and helps to inform the widest possible range of consumers.